The secret seven : Look out, secret seven - Blyton, Enid. (b, 2004)
What would the Seven do without Scamper the spaniel? First he discovers an unwanted visitor, then he protects the Seven as they spy on a thief late at night in Bramley Woods!
Keywords: Secret Seven (Fictitious characters) -- Juvenile fiction; Secret Seven (Fictitious characters).